Euclid: III. The NISP Instrument - Jahnke, K.; Gillard, W.; Schirmer, M.; Ealet, A.; Maciaszek, T.; Prieto, E.; Barbier, R.; Bonoli, C.; Corcione, L.; Dusini, S.; Grupp, F.; Hormuth, F.; et al. (EDP SCIENCES S A, 2025)
The Near-Infrared Spectrometer and Photometer (NISP) on board the Euclid satellite provides multiband photometry and R greater than or similar to 450 slitless grism spectroscopy in the 950-2020 nm wavelength range. In this reference article, we illuminate the background of NISP's functional and calibration requirements, describe the instrument's integral components, and provide all its key properties. We also sketch the processes needed to understand how NISP operates and is calibrated as well as its technical potentials and limitations. Links to articles providing more details and the technical background are included. The NISP's 16 HAWAII-2RG (H2RG) detectors with a plate scale of 0 ''.3 pixel(-1) deliver a field of view of 0.57 deg(2). In photometric mode, NISP reaches a limiting magnitude of similar to 24.5 AB mag in three photometric exposures of about 100 s in exposure time for point sources and with a S/N of five. For spectroscopy, NISP's pointsource sensitivity is a signal-to-noise ratio = 3.5 detection of an emission line with flux similar to 2 x 10(-16) erg s(-1) cm(-2) integrated over two resolution elements of 13.4 angstrom in 3 x 560 s grism exposures at 1.6 mu m (redshifted H alpha). Our calibration includes on-ground and in-flight characterisation and monitoring of the pixel-based detector baseline, dark current, non-linearity, and sensitivity to guarantee a relative photometric accuracy better than 1.5% and a relative spectrophotometry better than 0.7%. The wavelength calibration must be accurate to 5 angstrom or better. The NISP is the state-of-the-art instrument in the near-infrared for all science beyond small areas available from HST and JWST - and it represents an enormous advance from any existing instrumentation due to its combination of field size and high throughput of telescope and instrument. During Euclid's six-year survey covering 14 000 deg(2) of extragalactic sky, NISP will be the backbone in determining distances of more than a billion galaxies. Its near-infrared data will become a rich reference imaging and spectroscopy data set for the coming decades.